Digestible phosphorus levels for barrows from 50 to 80 kg - Viviane Maria Oliveira dos Santos Nieto; Charles Kiefer; Karina Márcia Ribeiro de Souza; Liliane Maria Piano Gonçalves; Marina de Nadai Bonin; Tânia Mara Baptista dos Santos; Kelly Cristina Nunes Carvalho; Alexandre Pereira dos Santos (Revista Brasileira de Zootecnia, 2016)
ABSTRACT This study was carried out to evaluate the levels of digestible phosphorus in diets for barrows with a high potential for lean meat deposition from 50 to 80 kg. Eighty barrows, with an initial weight of 47.93±3.43 kg, were distributed in completely randomized blocks, with each group given five levels of digestible phosphorus (1.86, 2.23, 2.61, 2.99, and 3.36 g kg−1). There were eight replicates, and two animals per experimental unit. Phosphorus levels did not significantly influence feed intake, weight gain, or feed conversion ratio. Daily digestible phosphorus intake increased linearly as levels of phosphorus in the diet were increased. Phosphorus levels did not significantly influence muscle depth, loin eye area, backfat thickness, or the percentage and quantity of lean meat in the carcass. A linear increase was observed for feeding cost as the levels of digestible phosphorus in the diet were increased, and the level of 1.86 g kg−1 cost 29.4% less when compared with the level of 2.61 g kg−1. The dry matter, natural matter, the coefficient of the residue, and volatile solids of the waste were not significantly influenced by phosphorus levels. Conversely, it was possible to observe an increasing linear effect for total solids, total phosphorus, and total nitrogen in the waste of animals receiving diets with increased levels of digestible phosphorus. The level of 1.86 g kg−1, which corresponded to a daily intake of 4.77 g−1 of digestible phosphorus, meets the requirements of barrows weighing 50 to 80 kg.